Pengaruh modal usaha, lama usaha, biaya produksi dan tenaga kerja terhadap pendapatan usaha kecil nanas di Desa Tangkit Baru - Teegar Dwi Putra; Syamsurijal Tan; Zainul Bahri (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the influence of business capital, business duration, production costs, and labor on the income of small-scale pineapple businesses in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency. Using a quantitative descriptive method with purposive sampling of 64 respondents, data were analyzed using multiple linear regression and SWOT analysis. The results show that: (1) The socioeconomic conditions of small-scale pineapple business operators are dominated by males (73.3%) with productive age 41-50 years (37.04%), high school education level (45.4%), and average income of Rp20-25 million per year (39.06%); (2) Partially, business capital (t=9.866; p=0.000), business duration (t=2.106; p=0.0395), production costs (t=5.253; p=0.000), and labor (t=5.060; p=0.000) have significant effects on income. Simultaneously, these four variables have a significant effect with F-statistic of 42.56 (p=0.000) and coefficient of determination (R²) of 74.26%; (3) SWOT analysis shows strengths position (1.80) higher than weaknesses (1.10), and opportunities (1.84) greater than threats (1.31), with SO, WO, ST, and WT strategies that can be implemented to enhance competitiveness and income sustainably.